Hybrid Adsorbent For In Situ Wastewater Treatment - Tavayogeshwary, Thangadurai (Universiti Sains Malaysia, 2017)
Inorganic/organic hybridization is usually used to synthesize functional materials. However, it is rarely considered in industrial wastewater treatment. By immobilizing the anionic (e.g. Acid Violet 7, Direct Blue 71)–cationic (e.g. Brilliant Green) dye complex with growing calcium carbonate, dye conjugate hybridization was presented. The structure of the conjugate hybrid were characterized by using Brunauer–Emmett–Teller (BET), Fourier transform infrared spectroscopy (FTIR), spectrophotometry and elemental analysis and the mechanism of formation was explained. The simple single-step hybridization applied in treatment of concentrated organic wastewaters. This technique involves adsorption, flocculation and ionic complexation and resulted a high level of removal of organic substances. By “using waste to treat waste”, a convenient, cost-effective and environment-friendly wastewater treatment was accomplished. This technique was tested by using industrial wastewater and river water. The best dye removal was obtained for the use of 1mM of Acid Violet 7 to treat 1mM of Brilliant Green which is 97.53% whereas for treating industrial waste sample, the highest dye removal of 83% with the 0.5mM of Direct Blue 71. This explained ion pair equilibrium between the anionic dye and cationic dye.